View of the Arches in the Mandapa of the Adinatha Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the arches in the mandapa (pillared hall) of the Adinatha Temple. The multi-colour arches have cartouche designs on the flanking pillars and the beams above the archway. The beams also have iron round rings. These might be used to attach temporary curtains or dividers.